Pengaruh Substitusi Tepung Ubi Jalar Ungu Terhadap Karakteristik Kue Kering - Helen C.D. Tuhumury; La Ega; Nuram Keliobas (Universitas Pattimura, 2018)
The objective of the study was to determine the concentation ratio between purple sweet potato flour and wheat flour in order to produce purple sweet potato cookies having particular nutritional content and preffered by consumers. A completely randomized experimental design was applied in this study. One experimental factor which was ratio of purple sweet potato flur and wheat flour consisting five level of treatments, was as signed i,e 100%: 0%, 80:20%, 60%:40%, and 20%: 80% respectively. Variables measured were chemical composition (protein, fat, moisture, anthocyanin content) and sensory properties (colour, taste, texture, overall likeness). Results showed that most variables were influenced by the ratio of sweet potato flour and wheat flour, excluding moisture content. The ratio of 80% sweet potato flour : 20% wheat flour resulted in cookies with good characteristics and mostly preffered by parelists. Anthocyamin content of this particular cookies (80%: 20%) was similar to that of sweet potato flour. Keywords: cookies, purple sweet potato flour, wheat flour ABSTRAK Penelitian ini bertujuan untuk menentukan konsentrasi tepung ubi jalar ungu dan tepung terigu yang tepat untuk menghasilkan kue kering ubi jalar ungu dengan kandungan gizi tertentu dan disukai. Rancangan yang digunakan adalah rancangan acak lengkap yang terdiri satu faktor dengan lima taraf perlakuan yaitu : Perbandingan tepung ubi jalar ungu dan tepung terigu 100% : 0%, 80% : 20%, 60% : 40%, 40% : 60%, 20% : 80%. Peubah yang di amati adalah komposisi kimia (penentuan kadar protein, kadar lemak, kadar air, kandungan antosianin) dan uji organoleptik (warna, rasa, tekstur, tingkat kesukaan). Hasil penelitian menunjukan bahwa perlakuan perbadingan tepung ubi jalar ungu dan tepung terigu mempengaruhi peubah-peubah yang diamati, sedangkan untuk kadar air tidak berbeda nyata. Berdasarkan hasil penelitian perlakuan perbandingan tepung ubi jalar ungu dan tepung terigu 80% : 20% dapat menghasilkan kue kering yang terbaik dan disukai. Kandungan antosianin kue kering ubi jalar dengan formulasi 80 : 20% tidak berbeda jauh dengan kandungan antosianin tepung ubi jalar. Kata kunci: kue kering, tepung terigu, tepung ubi jalar ungu